CMOS T/R switch design : towards ultra-wideband and higher frequency - Li, Qiang (2009)
This paper presents the comprehensive considerations of CMOS transmit/receive (T/R) switch design towards ultra-wideband and over 15-GHz frequencies. Techniques for